The Effect Probiotic Lactic Acid-Based on Organoleptic Indicators of Brown Rice Polish - Pradipta Bayuaji Pramono; Mohamad Haris Septian; Mikael Sihite (Journal of Livestock Science and Production, 2020)
This study aims to determine the effect of adding probiotics based on lactic acid bacteria (BAL) on brown rice polish fermentation, which was tested organoleptically. The variables observed were texture, colour, scent, flavor, and assessment of the quality of one month fermented brown rice polish. Sources of probiotics used are commercial probiotics based on lactic acid bacteria (LAB). The treatments given were P0 = Rice polish fermentation without the addition of probiotics (control), P1 = Rice polish fermentation + 0.5% probiotic, P2 = Rice polish fermentation + 1.0% probiotic, P3 = Rice polish fermentation + 1.5% probiotic. The data obtained were processed using variance analysis of a randomized complete design (RCD). If there were significant differences, the data was further tested using Duncan's Multiple Range Test (DMRT). The results showed that the addition of probiotics at a dose (0.5; 1.0; 1.5)% improved the flavor and quality assessment of the fermented brown rice polish but did not affect the texture, colour, and scent of fermented brown rice polish. It can be concluded that the addition of LAB-based probiotics can improve the quality of brown rice polish, which is assessed organoleptically.Keywords: Brown rice polish, Fermentation, Organoleptic, Probiotic